Community-Based Intervention Using Integrated Toga from Cultivation to Processed Products for the Prevention of Stunting in Toddlers in Sanggrahan Village - Rina Rina Sri Widayati; Nur Amalina; Suratman Suratman; Galih Pramuja inngam Fanani; Sintha Harlina Putri; Meidiana Nurul Aisyah; Bekti Setiyaningrum; Aulia Galuh Ani Sekar Arum; Dewangga Eka Saputra; Ilma Naisah Miftahul Jannah; Aulia uswatun Khasanah (Universitas Muhammadiyah Surakarta, 2026)
Stunting remains a major health problem in Sanggrahan Village, with 11 children under five recorded as stunted and an adolescent anemia prevalence of 57%. The village has strong potential resources, including 95 active health cadres, home gardens that can be utilized for family medicinal plants (TOGA) cultivation, and local institutions such as the Women Farmers’ Group (KWT) and the Village Health Post (PKD). The aim of this community service program (PKM) is to improve the knowledge, attitudes, and practices of health cadres and the community; develop natural resources such as home gardens and unused land; implement community midwifery service strategies; create a golden generation; improve the community’s economy; and encourage the use of website-based technology. The program was carried out using the Asset-Based Community Development (ABCD) method, which applies persuasive, educative, participatory, and normative approaches. The implementation included several stages: socialization, training, mentoring, technology application, and sustainability. The results showed significant improvements in the capacity of health cadres, KWT, and the community in managing TOGA and producing innovative herbal-based products such as ginger powder, moringa nuggets, and healthy moringa-based snacks. Village institutions were also strengthened through the establishment of a Nutrition Post (Pondok Gizi), while PKD played an important role in nutrition education, early detection of stunting, and the use of educational tools. In addition, the UMKM Expo proved effective in expanding promotion and marketing of local products. This community-based intervention generated a dual impact: improving community health status through stunting prevention while simultaneously fostering economic independence. As a follow-up, continuous mentoring, product diversification, quality standardization, and strengthening of marketing networks are recommended to optimize and enhance program competitiveness. The synergy between KWT and PKD may serve as a sustainable empowerment model based on local potential and village wisdom.